Factors affecting teachers’ emotion in teaching: A narrative inquiry at a high school = Nghiên cứu về cảm xúc của giáo viên đối với hoạt động dạy học qua tự thuật của giáo viên trung học phổ thông - Nguyễn, Thi Thu Uyên (2020)
The study aimed to provide an in-depth analysis of the causes that were influential towards emotion of the teachers who were selected from different high school. The study was adopted as a qualitative research method and the narrative inquiry was used. The data of the study were collected with participants’ narratives. Content analysis method was used in analyzing the data. In accordance with the research aims, this study identified 4 themes. As a result of the coding of the data obtained at the end of the research, the following 4 themes. (1) Professional commitment, (2) Students, (3) Collegiality, (4) Financial were determined as the four themes of the study. Through all these can be illustrated the role of emotions on the teaching work. They are part of working environment and definitely affect with various ways. Either positive either negative its research help to elicit the keys for success and to avoid non desired results on workplace.